Appraising the therapeutical potentials of Alchornea laxiflora (Benth.) Pax & K. Hoffm., an underexplored medicinal herb: A systematic review - Jain, Nem Kumar; Tailang, Mukul; Kumar, Santosh; Chandrasekaran, Balakumar; Alghazwani, Yahia; Chandramoorthy, Harish C.; Kumar, Ashish; Deshpande, Hemali; Wal, Pranay; Balamurugan, Manickam; Chidambaram, Kumarappan (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Alchornea laxiflora (Benth.) Pax & K. Hoffm. (A. laxiflora) which belongs to the Euphorbiaceae family, has long been used in traditional African medicine as a cure for teething problems, malaria, fibroid, tumour, sickle cell anaemia, menstrual disorder, skin problems, anxiety, epilepsy, venereal diseases, diabetes, hypertension, and gastrointestinal disorders. Material and methods: The scientific name of the plant was validated using ‘The Plant List’, ‘Kew Royal Botanic Gardens’ and Tropicos Nomenclatural database. The literature search on A. laciflora was performed using electronic search engines and databases such as Google scholar, ScienceDirect, PubMed, AJOL, Scopus, and Mendeley. Results: To the best of our knowledge, no specific and detailed review has been reported on A. laxiflora. Consequently, this review provides an up-to-date systematic presentation on ethnobotany, phytoconstituents, pharmacological activities, and toxicity profiles of A. laxiflora. Phytochemical investigations disclosed the presence of important compounds such as; alkaloids, flavonoids, phenolics, terpenoids and fatty acids. Further, various pharmacological activities, and traditional uses reported for the herb were discussed comprehensively. Conclusion: This systemic review presents the current status and perspectives of A. laxiflora as a potential therapeutic modality that would assist future researchers in exploring this African herb as a source of novel drug candidates for varied diseases.